Influence of the Relations to Self of Older Secondary School Pupils to Their Tolerance - Sprindžiūnas, Andrius (Acta Paedagogica Vilnensia, 2001)
The aim of this article is to reveal main correlations among most important indicators of older pupils• positive relations with themselves (self-understanding, self-esteem, self-sympathy and expectation of others’ positive attitude) and some peculiarities of their tolerance. The statistical analysis revealed significant correlations among these inner factors and some indicators of the pupils’ understanding tolerance and their tolerant behaviour with their peers, parents and teachers. Thus, the research data revealed that approx. One third part of the older pupils do not understand or respect themselves properly.